Modern trends in recycling waste thermoplastics and their prospective applications: a review - Oladele, Isiaka Oluwole; Okoro, Christian Junior; Taiwo, Anuoluwapo Samuel; Onuh, Linus N.; Agbeboh, Newton Itua; Balogun, Oluwayomi Peter; Olubambi, Peter Apata; Lephuthing, Senzeni Sipho (MDPI, 2023)
Thermoplastics and thermosetting plastics are two major classes of polymers in that have recently become materials that are indispensable for humankind. Regarding the three basic needs of human beings—food, shelter, and clothing—polymers and polymer-based materials have gained pre-eminence. Polymers are used in food production, beginning with farming applications, and in the health sector for the development of various biomaterials, as well as in shelter and clothing for a variety of applications. Polymers are the material of choice for all modern-day applications (transportation, sporting, military/defence, electronics, packaging, and many more). Their widespread applications have created many negative challenges, mainly in the area of environmental pollution. While thermoplastics can be easily reprocessed to obtain new products, thermosetting plastics cannot; thus, this review focuses more on the use of waste from thermoplastics with less emphasis on thermosetting plastics. Hence, the review presents a concise summary of the availability of waste thermoplastics as raw materials for product development and the anticipated benefits. The prospects for waste thermoplastics and thermosetting plastics, the possibility of cleaning the environment, and the uncovering of opportunities for further research and development are presented. The limitations of the current methods of waste polymer recycling are highlighted with possible future prospects from newly introduced methods. With zero tolerance for polymer waste in our environments, potential uses for recycled thermosetting plastics are described. Waste polymers should be seen as potential raw materials for research and development as well as major materials for new products. Recycled polymers are expected to be processed for use in advanced materials applications in the future due to their availability. This review shows that the major source of environmental pollution from polymers is the packaging, hence the need to modify products for these applications by ensuring that most of them are biodegradable.
Keywords: waste polymers; recycling; environmental pollution; future applications